Statistical Evaluation of Moving Observer Method Accuracy for Measuring Traffic Flow Variables on Urban Roads - Al-Bahr, T. (Institute of Electrical and Electronics Engineers Inc., 2021)
The accuracy of traffic data collected from the field is an essential requirement for effective and reliable outcomes for planning, design, operation and assessment of transportation facilities. Moving Observer Method (MOM) is one of the well-known techniques that is widely used for generation of traffic data on urban roads due to its cheapness and ease of field application. However, the accuracy of the data collected using MOM is sensitive to the fluctuation of traffic flow demand, especially, on urban road. This study aims to statistically evaluate the traffic flow collected using MOM on urban road. A representative urban road segment in Johor Bahru was chosen for this study. The chosen road section has five (5) major access points of driveways and intersections. Traffic flow was concurrently measured on the selected urban road segment using both manual (with the aid of field observers) and MOM approaches over a duration of 90 minutes. Traffic flow estimates from the two approaches were compared statistically. A null hypothesis put forth is that there is no significant difference between the traffic estimates from the techniques. A statistical analysis using Z-standard normal distribution at 90 confidence level affirmed the postulated hypothesis, which implies that there exists no statistically significant difference between the traffic flow estimates derived from the two methods. This finding suggests that MOM can reliably be applied to estimate traffic flow on urban roads with reasonable accuracy. Â© 2021 IEEE.